Good Corporate Governance dan Tanggung Jawab Sosial Perusahaan (Corporate Social Responsibility) - Khairani Siregar; Ovia Tinalita Tarigan; Jenny Panjaitan; Annastasya Siregar; Anggi swintaro; Wilchan Robain (PT Pustaka Cendekia Group, 2025)
The evolution of corporate governance was the root cause of the crises that rocked major American and Indonesian companies. This massive corporation is in jeopardy because to its lax corporate governance norms, its mergers with several big banks, and the environmental damage that various corporations involved with natural resources have caused the government to pay for. Poor corporate governance in the US is mostly attributable to the behaviour of upper management, as was shown at Enron. Aiming to promote an efficient market and transparency, successful corporate governance adheres to the ideals of fairness, accountability, responsibility, and openness. Practicing corporate social responsibility is an astute approach to managing a company. A report called sustainability reporting should be prepared and included in the company's annual report to record the implementation. Companies that care about their communities and work to improve it show that they have good corporate governance practices.